STAGING STRUCTURE OF PLAY "ADONG PULANG" PETTA PUANG PLAY TROUPE IN SOUTH SULAWESI - Andi Baetal Mukadas (JURNAL PAKARENA, 2021)
This study aims to provide a specific description of the Performance Structure of the Play "Adong Pulang" for the Petta Puang Play Troupe in South Sulawesi. This study uses a qualitative approach, the data obtained through the method of observation, interviews and documentation. The purpose of this study is to understand in detail and then describe the structure of the play "Adong Pulang" for the Petta Puang Play Troupe in South Sulawesi. To explore the problems in this research, a structure and texture analysis approach will be carried out as well as Thomas Munro's aesthetic elements which include ideas, details, elements, composition, structure, interwoven elements. All these aesthetic elements in theatrical performances are manifested through plot, characterization, theme, dialogue, scene, costumes, lighting, setting, property and music. This study concludes that the structure of the theater performance of “AdongPulang” for the PettaPuang Sandiwara Group in South Sulawesi is not tied to the concept of determinants, meaning that the show relies more on improvisation which is built through loose dialogues and responses from the audience. In addition, several general theater concepts are no longer a reference in the show, but appear as they please, as they are with one principle that is important for the audience to be entertained